2019
DOI: 10.1017/s0305000919000722
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between working memory and complex syntax in children with Developmental Language Disorder

Abstract: Some theories of Developmental Language Disorder (DLD) explain the linguistic deficits observed in terms of limitations in non-linguistic cognitive systems such as working memory. The goal of this research is to clarify the relationship between working memory and the processing of complex sentences by exploring the performance of 28 French-speaking children with DLD aged five to fourteen years and 48 typically developing children of the same age in memory and linguistic tasks. We identified predictive relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 97 publications
10
75
0
6
Order By: Relevance
“…Concerning syntax, based on what has been observed in studies on TD children (Friedmann et al, 2009) and children with DLD (Friedmann & Novogrodsky, 2011), we predict that (1) a significant intervention effect will be found in the accuracy measurements of children with SLD, and that the computational complexity associated with the presence of intervention will lead to a decrease in accuracy and (2) the intervention effect will be stronger for children with SLD than it is for TD children, as limited WM resources in the SLD group should influence how these children process complex syntax. Concerning WM, we predict that (1), as was found by Helland and Asbjørnsen (2004), children with SLD will have complex span limitations, demonstrated by poor backward digit span performance, and (2) complex span and the comprehension of structures containing NP-intervention will be correlated in SLD, as was the case for DLD (Delage & Frauenfelder, 2020; Montgomery & Evans, 2009; Montgomery et al, 2008).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Concerning syntax, based on what has been observed in studies on TD children (Friedmann et al, 2009) and children with DLD (Friedmann & Novogrodsky, 2011), we predict that (1) a significant intervention effect will be found in the accuracy measurements of children with SLD, and that the computational complexity associated with the presence of intervention will lead to a decrease in accuracy and (2) the intervention effect will be stronger for children with SLD than it is for TD children, as limited WM resources in the SLD group should influence how these children process complex syntax. Concerning WM, we predict that (1), as was found by Helland and Asbjørnsen (2004), children with SLD will have complex span limitations, demonstrated by poor backward digit span performance, and (2) complex span and the comprehension of structures containing NP-intervention will be correlated in SLD, as was the case for DLD (Delage & Frauenfelder, 2020; Montgomery & Evans, 2009; Montgomery et al, 2008).…”
Section: Introductionmentioning
confidence: 74%
“…However, children with SLD have been associated with both simple and complex span limitations, and Helland and Asbjørnsen (2004) showed that children with literacy deficits and children with comorbid literacy and numeracy deficits were more likely to be impaired in complex span (measured by the backward recall of digits) than in simple span (measured by the forward recall of digits). Furthermore, empirical evidence suggests that a specific relationship exists between complex span and the comprehension of complex syntax, and that complex span capacity might be a better indicator of how complex structures are processed in atypical populations, such as in children with DLD (Delage & Frauenfelder, 2020; Frizelle & Fletcher, 2015; Montgomery & Evans, 2009; Montgomery et al, 2008). For this reason, we focus exclusively on complex span in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Both children with ADHD and DLD performed poorly on the attention shifting measures but only children with DLD demonstrated WM vulnerability. There is robust empirical evidence demonstrating that WM deficits limit the ability of children with DLD to process complex morphosyntax (e.g., Delage and Frauenfelder, 2020), but it seems to be the case that deficits in attention shifting are insufficient to lead to the degree of morphosyntactic impairment associated with DLD. Otherwise, we would have expected children with ADHD to perform poorly on both morphosyntax tasks.…”
Section: Discussionmentioning
confidence: 99%
“…There is also substantial evidence for simple and complex span impairments in children with DLD (e.g., Majerus et al, 2009;Delage and Frauenfelder, 2020). In particular, Majerus et al (2009) found that French-speaking children (N = 12, M = 8;4) with DLD struggle to perform simple span tasks that required them to reconstruct the serial order of a list of items, findings that were replicated by Delage and Frauenfelder (2020) with a larger sample (N = 28, M = 8;10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation